2016
DOI: 10.1002/ppul.23469
|View full text |Cite
|
Sign up to set email alerts
|

Albuterol via metered-dose inhaler in children: Lower doses are effective, and higher doses are safe

Abstract: Higher albuterol dosage regimens did not result in lower admission rate or shorter length of stay in the ER, but showed similar safety profile for children with moderate to severe acute asthma. Pediatr Pulmonol. 2016;51:1122-1130. © 2016 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Consequently, under the force of concentration gradients, AS release followed the same kinetic law. Since AS is a-first-line agent for treatment and prevention of bronchospasm in patients with asthma and chronic obstructive pulmonary disease,62,63 the pharmacodynamic properties of AS-BSA-NPs should confer benefits to these patients via the targeted and rapid release of a bronchodilator after NPs arrive at the distal bronchi. Large hollowed NP aggregates have many merits, including prolonging drug release, enhanced drug utilization, and alleviation of administration frequency, giving rise to improved patient compliance 64,65.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, under the force of concentration gradients, AS release followed the same kinetic law. Since AS is a-first-line agent for treatment and prevention of bronchospasm in patients with asthma and chronic obstructive pulmonary disease,62,63 the pharmacodynamic properties of AS-BSA-NPs should confer benefits to these patients via the targeted and rapid release of a bronchodilator after NPs arrive at the distal bronchi. Large hollowed NP aggregates have many merits, including prolonging drug release, enhanced drug utilization, and alleviation of administration frequency, giving rise to improved patient compliance 64,65.…”
Section: Discussionmentioning
confidence: 99%
“…Although our intervention increased MDI dosing, studies have shown conflicting results about whether there is clinical benefit to using a larger dose of albuterol. [15][16][17] A 2016 randomized trial compared large-dose albuterol to small dose in children with moderate to severe asthma in the ED and found no significant differences in LOS, admission rate, and safety profile. 15 Another study comparing a single, large dose (6-10 puffs) of albuterol to small dose (2 puffs) in children with mild acute asthma showed a non-significant larger improvement in forced expiratory volume in 1 second for the large-dose group.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, under the force of concentration gradients, AS release followed the same kinetic law. Since AS is a-first-line agent for treatment and prevention of bronchospasm in patients with asthma and chronic obstructive pulmonary disease, 62 , 63 the pharmacodynamic properties of AS-BSA-NPs should confer benefits to these patients via the targeted and rapid release of a bronchodilator after NPs arrive at the distal bronchi. Large hollowed NP aggregates have many merits, including prolonging drug release, enhanced drug utilization, and alleviation of administration frequency, giving rise to improved patient compliance.…”
Section: Discussionmentioning
confidence: 99%